Thermal study of mononuclear Pd(II) complexes of the type [Pd(X)(2)(Rtu)(PPh3)] (X = Cl, SCN; Rtu = N-methylthiourea, N-phenylthiourea) - Arantes, Francisco C. C. [UNESP]; Moro, Antonio C. [UNESP]; Klein, Iolanda S. [UNESP]; da Silva, Cristiana [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Mauro, Antonio Eduardo [UNESP]; Nogueira, Vânia Martins [UNESP] (Springer, 2011)
The synthesis, spectroscopic characterization, and thermal analysis of the compounds [Pd(X)(2)(mtu)(PPh3)] (X = Cl- (1), SCN- (2); mtu = N-methylthiourea; PPh3 = triphenylphosphine) and [Pd(X)(2)(phtu)(PPh3)] (X = Cl- (3), SCN- (4); phtu = N-phenylthiourea) are described. The thermal decomposition of the compounds occurs in two, three, or four stages and the final decomposition products were identified as Pd-0 by X-ray powder diffraction. The thermal stability order of the complexes is 4 > 3 > 2 > 1.
Keywords: Palladium (II) compounds; Thioureas; Pseudohalides; Thermal analysis